Effect of Classical Eberhart Lime Kiln Modifications on Capacity and Lime Quality of Kilns. - ANIL, MESUT; TURKMENOGLU, MEHMET; YAPICI, NIL; PINARBASI, AHMET; KILIC., OZEN (Asian Journal of Chemistry, 2010)
While there are various factors affecting lime quality, the quality of raw material, calcination temperature and calcination time as well as the fuel type used are among most important factors. Some modernization activities were performed in classical Eberhart type lime kilns of a facility that is located in the city of Adana, Turkey. In this context, alterations were done in kiln heights of this facility and both new stack system and stack gas treatment units were mounted in the facility and in this way, polycyclic aromatic hydrocarbons (PAHs) having carcinogenic effect were anulled by keeping them at 900 ºC for at least 0.3 s. Loading raw materials and fuel into kilns through an automated system and similarly, loading unburned lime from kiln base to unburned lime bunker automatically have provided considerable advantages. The used kiln limestone was investigated in detail both under laboratory conditions and kiln regime calcination conditions and the factors affecting lime quality were determined through plenty of surface area, porosity measurements and chemical analysis. It was observed that, depending on the limestone content, dissolution accelerates after 850 ºC and when 900 ºC is reached for pure limestone in kiln applications, it is understood that the calcination is completed. Some of porosities which are opened in sections exposed to calcination for a long time in higher temperatures are blocked. In applications where it was understood that MgO and other impurities within the limestone are effective on the quality, it was seen calcination process was completed at low temperatures for limestone having more than 5 % MgO content. Due to aforementioned alterations performed on 8 modernized Eberhart type kilns of partner facility of this project, Nur Kirec Ltd. Sti., the facility now in a position to obtain emission license. In addition, capacity of this facility increased by 20 % active CaO ratios in produced quick lime has reached up to an average value of 92.